Printmaking a contemporary perspective - Coldwell, Paul (Black Dog Publishing Ltd., 2010)
"Printmaking A Contemporary Perspective provides a comprehensive overview of printmaking in all its forms, from seventh century woodcuts to the most recent developments in digital technologies. Clearly organised, the book covers the history and developments of various printmaking techniques, including relief printing, intaglio, lithography, screenprinting and digital print. Printmaking A Contemporary Perspective then goes on to feature the work of contemporary artists from around the world working with print, covering topics as varied as hybrid printmaking techniques and practices, and the political imperatives informing the work of artists and printmaking studios. Generously illustrated throughout, Printmaking A Contemporary Perspective is an up-to-date and essential survey for anyone interested in printmaking and contemporary fine art practice." -- Provided by publisher